2018
DOI: 10.4081/gh.2018.689
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of asbestos exposure and occupational health care in Poland during the period 2004-2013

Abstract: Asbestos is carcinogenic to humans and exposure to this substance can cause a wide range of diseases. In Poland 1997, a statutory ban was introduced on the production, use and marketing of products containing asbestos. The National Programme for Asbestos Abatement for 2009-2032 includes scheduled activities considering asbestos exposure assessment and health protection. As there are several data sources for asbestos exposure in Poland, which are not linked, the aim of this study was to gather and order them de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The analysis of measurements of asbestos fibre concentrations in the air in the period 2004–2013 was made on the basis of data provided by the Ministry of Economy [54]. Measurements of asbestos fibre concentrations were undertaken in 279 counties, which constitute 73% of the total number of counties in Poland (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of measurements of asbestos fibre concentrations in the air in the period 2004–2013 was made on the basis of data provided by the Ministry of Economy [54]. Measurements of asbestos fibre concentrations were undertaken in 279 counties, which constitute 73% of the total number of counties in Poland (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Data from an Italian study showed that the hospitalized patients were mostly men and elderly from the north-west region of the country [6]. In Poland, the majority of the former asbestos-producing plants are located in the southern part of the country [14], which may be an important factor relating to the higher number of asbestosis cases in this region of Poland. Another study reported that all patients who were not exposed to asbestos at work or were exposed to lower quantities of the substance, died of mesothelioma, although there were also other factors that caused the death of factory workers (lung cancer, asbestosis) [19].…”
Section: Discussionmentioning
confidence: 99%
“…A study on the incidence of occupational diseases related to asbestos in Poland in 970-2015, reported 4,983 asbestos-related disease cases, of which asbestosis, lung cancer, mesothelioma, diseases of the pleura and pericardium were the most common. There are other papers with information on asbestosis in Poland [13,14,15], but (to the authors' knowledge) the presented study is the first which can shed light on the current burden of this disease.…”
Section: Introductionmentioning
confidence: 98%
“…Statistical models are used to assess the potential risk of asbestos-related diseases, e.g., pleural mesothelioma [8] or lung cancer [9], based on the total amount of asbestos fibers used in the production per country population. Due to the lack of data on the quantity and the spatial distribution of asbestos-cement products used, research is undertaken to assess the risk of developing asbestos-related diseases on the basis of asbestos consumption indices in production per country's population [10,11]. There is a lack of detailed data on the number of products used, spatially broken down into administrative units, which could significantly affect the obtained results [12].…”
Section: Introductionmentioning
confidence: 99%